2004
DOI: 10.1128/mcb.24.5.2025-2040.2004
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Translational Regulation Mediated by the α Subunit of Eukaryotic Initiation Factor 2 Inhibit Antiviral Activity and Facilitate the Malignant Transformation of Human Fibroblasts

Abstract: Suppression of protein synthesis through phosphorylation of the translation initiation factor ␣ subunit of eukaryotic initiation factor 2 (eIF2␣) is known to occur in response to many forms of cellular stress. To further study this, we have developed novel cell lines that inducibly express FLAG-tagged versions of either the phosphomimetic eIF2␣ variant, eIF2␣-S51D, or the phosphorylation-insensitive eIF2␣-S51A. These variants showed authentic subcellular localization, were incorporated into endogenous ternary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 76 publications
3
46
1
Order By: Relevance
“…These findings are in contrast to conclusions recently derived from observations using an inducible overexpression system to produce S51A and S51D mutants of eIF2␣ (56). These studies did not detect a complete reduction in protein synthesis that would be expected with S51D eIF2␣ expression (33).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in contrast to conclusions recently derived from observations using an inducible overexpression system to produce S51A and S51D mutants of eIF2␣ (56). These studies did not detect a complete reduction in protein synthesis that would be expected with S51D eIF2␣ expression (33).…”
Section: Discussioncontrasting
confidence: 99%
“…The sensitivity of VSV translation to eIF2␣ phosphorylation is fully consistent with previous reports showing that the activation of PKR (12,27) and the subsequent phosphorylation of eIF2␣ (24,26) is an important host defense mechanism against VSV infection. These studies showed that removing PKR or keeping eIF2␣ phosphorylation from blocking eIF2 function allows enhanced VSV replication.…”
Section: Discussionsupporting
confidence: 91%
“…121,122 To further clarify the role of eIF2a in apoptosis, transformation and gene regulation, our own laboratory developed inducible, murine cell lines expressing a phospho-mimetic eIF2a variant (eIF2a-S51D) and the phosphorylation-insensitive eIF2a-S51A variant. 123 Through this approach, we observed a reproducible and distinct change in the cellular morphology of both the eIF2a-S51D-and the eIF2a-S51A-expressing cell lines, for reasons that remain unclear. 124 Expression of the eIF2a-S51A variant resulted in a very mild increase in growth rates.…”
Section: Mechanisms Of Pkr Actionmentioning
confidence: 93%
“…However, cells inducibly expressing eIF2a-S51D did not undergo rapid apoptosis. 123 Thus, it appears that at least in a 3T3 L1-inducible system, the eIF2a-S51D mutant causes a modest elevation in 'background' cell death, but does not induce global cell death. Further, apoptosis in response to well-characterized stimuli such as TNFa was also unaltered by expression of either of the eIF2a variants.…”
Section: Mechanisms Of Pkr Actionmentioning
confidence: 98%
See 1 more Smart Citation